Implementation of Character Education in Elementary Schools of Tanjung Agung District, Muara Enim Regency - Pangesti, Tria (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to describe the implementation of character education in elementary schools. This research was conducted at SD Negeri 3 Tanjung Agung which is located at Jalan Lintas Baturaja, Pulau Panggung Village, Tanjung Agung District, Muara Enim Regency, South Sumatra Province. This research was conducted starting from February to May 2022. Collecting data and information obtained by researchers while in the field by directly obtaining surveys and documentation. The results state that almost all students can implement character education in elementary schools with habituation that is scheduled and used by school teachers.